Pengaruh Broadscope, Agregation, Timeliness dan Integration Terhadap Kinerja Manajerial Pada PT Pos KC Tulungagung - Annuha, Faizah; Priantilianingtiasari, Ruly (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
This study was conducted to determine the effect of the influence of broadscope, aggregation, timeliness and integration on managerial performance at PT POS KC Tulungagung. This research uses quantitative methods with analysis methods using multiple regression. The data in this study are data obtained from respondents of PT POS KC Tulungagung by sampling 100 respondents. The results of the study prove that broadscope, timeliness and integration have an influence on managerial performance. The results of testing the t test hypothesis show that the broadscope t count of 7.759 is greater than the t table value of 1,664 or the sig value of 0.000 <0.05 partially broadscope has a significant impact and has a managerial performance relationship at PT POS KC Tulungagung. The t value of aggregation 0.922 is less than the t table value of 1,664 or the sig value of 3.59> 0.05 partially aggregation has no effect and has no relationship to managerial performance at PT POS KC Tulungagung. Tulungagung. These results are not in line with previous research, due to differences in research locations and managerial functions in the company. The calculated t value of timeliness 2.365 is more than the t table value of 1,664 or the sig value of 0.020 <0.05 partially timeliness has a significant effect and has a relationship to managerial performance at PT POS KC Tulungagung. The t value of integration count 4.325 is more than the t table value of 1,664 or sig of 0.000> 0.05 partially integration has a significant effect and has a relationship to managerial performance at PT POS KC Tulungagung. Meanwhile, the results of the F test (simultaneous) obtained F count 50.979 and F table of 2.467 which means that broadscope, aggregation, timeliness and integration together have a significant effect on the managerial performance of PT POS KC Tulungagung. These results are not in line with previous research, due to differences in research locations and managerial functions in the company.